The effect of transient state rainfall on stability of a residual soil slope - Kassim, Azman; Gofar, Nurly; Mokhtar, Noraieni; Lee, Min Lee (2006)
Slope instability attributable to rainfall occurant is a common geotechnical problem in tropical asian countries specially Malaysia. Many slope stability studies have illustrated the effect infiltration various hydrological characteristic of the soil in addition to climatic information. To futher understand the effect of rainfall, numerical modelling is commonly used to study how infiltration into slope varies with respect to rainfall intensity and how this infiltration affect the stability of slope. This paper attempts to identify the effect of transient state rainfall stability of a common residual soil slope during specific rainfall duration. A numerical modelling of the case study is presented to stimulate the changes in pore-water pressure due to different rainfall patterns and this are used to calculate the factor of safety of the slope. The result demonstrate that the transient state rainfall does play an important role in slope stability.